Enhancing Community Participation in Local Development Projects: The Bangladesh Context - Ara, Esmat; Seddiky, Md. Assraf; Basit, Abdul; Khanam, Ruba (European Scientific Journal, ESJ, 2024)
This paper focuses on developing an approach for effective community participation in local development projects. Researchers conducted a field study in Sunamganj district, one of the most vulnerable areas in Bangladesh, and collected information from 54 respondents, including Union Parishads (UP) chairpersons and members, secretaries, committee members, and local beneficiaries through interviews and FGDs using purposive sampling. Researchers also collected relevant documents from the Union Parishad (project plan, evaluation report, and annual progress report) to compare the information obtained from the participants in the field and analyzed them using the thematic analysis method. Study findings revealed that although UP is considered a close-knit community-based organization due to the nature of its development work and geographic location, inclusive decentralization and a democratic environment have not been established at the local level institutions to enhance meaningful community participation in development projects. This deficiency is attributed to outsider interferences, nepotism, lack of knowledge and information, top-down bureaucratic decisions, gender discrimination, and corruption. It is believed that the model of a meaningful decentralized participation system would help mobilize the comprehensive local development process.